Employee’s Dilemma – How Meaningfulness in Work Can Influence Gen Z to Stay in Organization - Azzahra, Hurul A'ini Sekar; Ambalika, Ni Komang Ayu Diah; Adipratama, Yulianto Wahyu Putra (IJBLE Scientific Publications Community Inc., 2025)
Retaining Generation Z (Gen Z) employees is an organizational challenge due to their low loyalty and high expectations for work-life balance. Meaningfulness in work is considered to contribute to increasing their intention to stay in the organization. To examine the influence of knowledge sharing system and job crafting on meaningfulness in work and intention to stay of Gen Z employees. The data was analysed using statistical techniques to test the relationship between variables. The results of the analysis show that all hypotheses in this study are significantly supported. The Knowledge Sharing System plays an important role in improving job crafting, meaningfulness in work, and employee intention to stay. In addition, job crafting not only increases the meaning of work but also contributes directly to employee loyalty to the organization. Effective job crafting and knowledge sharing system management can increase the meaning of work, strengthen Gen Z's loyalty to the organization.